Penerapan Digital Marketing pada Gopool Billiard & Cafe - Michelle Michelle; Listia Nurjanah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study focuses on the implementation of digital marketing strategies at GoPool Billiard & Café to enhance business appeal and leverage digital platforms, particularly social media, as the primary means of promotion. In an era of rapid digital growth, social media has become an effective tool for reaching a wider audience of potential customers and building strong relationships with them. The methods used in this research include interviews and documentation to obtain in-depth information and record the process of implementing digital marketing strategies. The results of the study indicate that utilizing social media platforms like Instagram and TikTok can increase customer interaction, expand audience reach, and strengthen the brand identity of GoPool Billiard & Café. This strategy has proven effective in attracting new customers while retaining the loyalty of existing ones through creative, informative, and consistent content.